Information literacy and social justice : radical professional praxis - Gregory, Lua.; Higgins, Shana (Sacramento, CA : Library Juice Press, 2013)
"Discusses information literacy and its social justice aspects, through a selection of chapters addressing the values of intellectual freedom, social responsibility, and democracy in relation to the sociopolitical context of library work"--Provided by publisher.
The violence of information literacy : neoliberalism and the human as capital / Nathaniel F. Enright -- The neoliberal library / Maura Seale -- You've got to know and know properly : citizenship in Kazuo Ishiguro's Never let me go and the aims of information literacy instruction / Jeff Lilburn -- From "A crusade against ignorance" to a "Crisis of authenticity" : curating information for a participatory democracy / Andrew Battista -- Critical information literacy in the college classroom : exploring scholarly knowledge production through the digital humanities / Andrea Baer -- The tyranny of tradition : how information paradigms limit librarians' teaching and student scholarship / Carrie Donovan and Sara O'Donnell -- The three-credit solution : social justice in an information literacy course / Anne Leonard and Maura A. Smale -- Hip-hop and information literacy : critically incorporating hip-hop in information literacy instruction / Dave Ellenwood -- Forces of oppression in the information landscape : free speech and censorship in the United States / Lua Gregory and Shana Higgins -- Critical legal information literacy : legal information as a social construct / Yasmin Sokkar Harker -- Information power to the people : students and librarians dialoguing about power, social justice, and information / Amanda J. Swygart-Hobaugh -- Information literacy and service-learning : creating powerful synergies / Christopher A. Sweet -- The public academic library : friction in the teflon funnel / Patti Ryan and Lisa Sloniowski.
Bibliografske bilješke iza svakog rada. Kazalo.
Keywords: informacijska pismenost; socijalna pravda; knjižničarstvo - društveni aspekti; knjižničarstvo - društvena angažiranost